Integrasi Pendekatan Antropometri dan Metode RULA dalam Perancangan Meja Ragum Ergonomis untuk Praktikum Kerja Bangku - Wirakusuma, Kadex Widhy; Aifah, Nur; Padang, Ricard Lawang (Politeknik ATI Padang, 2025)
The bench vise table used in benchwork practice activities has not been ergonomically designed, which can lead to awkward postures and increase the risk of musculoskeletal disorders among students. Ergonomics is a crucial factor in improving comfort, efficiency, and safety during manual work. This study was conducted to design an ergonomic bench vise table by integrating anthropometric data with the Rapid Upper Limb Assessment (RULA) method. The research applied a descriptive-quantitative approach with 83 students selected from a population of 104 using Slovin’s formula. Anthropometric measurements were taken to obtain body dimensions, a Nordic Body Map (NBM) questionnaire was distributed to identify musculoskeletal complaints, and posture assessments were conducted using the RULA method. Data were analyzed with normality, uniformity, and adequacy tests, and percentile values (P5–P95) were used as the basis for the table design. The results revealed that the existing bench vise table surface was on average 12.5 cm below the students’ elbow height, which produced a RULA score of 6, categorized as high risk and requiring immediate improvement. Anthropometric analysis indicated elbow height values of P5 = 76.02 cm, P50 = 86.20 cm, and P95 = 96.38 cm. These values were used to propose a new bench vise table design with adjustable height in the range of 76.02–96.38 cm. Evaluation of the proposed design demonstrated a reduction in the RULA score from 6 to 2, signifying a shift from high risk to low risk. The findings suggest that an ergonomically designed adjustable bench vise table can significantly improve working posture, minimize musculoskeletal risks, and enhance learning conditions in benchwork practice. Further studies are recommended to test the structural stability, load capacity, and user satisfaction of the proposed design.